Desenvolvimento de um sistema para criação de laudos estruturados - Costa, Lorena Dutra da (2018)
A gradual change is underway in the radiology for the use of structured reports based on radiological imaging. Recent studies indicate that structured reports offer several advantages over reports without a standard for their creation, such as greater clarity, consistency and end-user satisfaction. One of the objectives of this research is to propose a structured diagnostic model for the diagnosis by imaging and to investigate if the use of this type of document for the exams is presented as a clinically relevant advantage. This study was developed by a research group called Applied Computing in Health (CA + SA), through a collaboration between the Applied Computing Laboratory (LaCA) of the Federal University of Santa Maria (UFSM) and the Radiodiagnostic Unit of the University Hospital of Santa Maria (HUSM). In this way, the research was developed jointly, between professionals of the technological area and professionals in the health area. During the entire execution of this study the discussion of the clinical necessities was included together with the specialists. A system was developed that allows the creation of structured reports using the proposed model and through evaluations carried out by the HUSM team involved in the research. As a result, it was found that the use of pre-ready templates improves the reporting process, reducing the time the documents are created. At the end of the research development process the result was the obtaining of an image diagnostic template / template that can be used to optimize the process of creating new reports using the developed system.